Prevalence of carbapenemase-producing Klebsiella pneumoniae isolates in Belarus and their competitive ability - Tapalskiy D.V.; Petrenyov D.R. (Клиническая микробиология и антимикробная химиотерапия, 2017)
Susceptibility to antibiotics was determined for 208 hospital isolates from 4 regions of Belarus. The broad abundance of resistance to carbapenems was shown. The genes of carbapenemases blaNDM, blaOXA-48 and blaKPC were detected in 55 strains from 12 multifield hospitals in 4 cities. The reduced velocity of exponential growth and low competitive ability were revealed in carbapenemase-producing isolates in comparison to drug susceptible strains of K. pneumoniae.